Improvement of clay slurry using chemical agents - Zheng, Peigang (2016)
Marine clay has many engineering difficulties on site due to its low undrained shear strength. It is unable to provide a stable working platform for machineries and labours prior to any treatment. Singapore has many reclaimed land area, and will be carrying out more land reclamation to attain more land space. In this report, the effect of using chemicals to improve marine clay’s shear strength, permeability and other soil properties was investigated in detail. The key focus will be on the shear strength and permeability of treated marine clay with lime or polyacrylamide (PAM). The objective of this project is to investigate the possibility of using chemicals to improve the shear strength, permeability and other soil properties of marine clay. Two chemicals were used in this project, namely lime and PAM. The PAM used can be divided into three categories: anionic, non-ionic and cationic. A preliminary test on PAM is conducted to determine the type of PAM which can accelerate the sedimentation of marine clay. The anionic PAM is chosen from the preliminary tests for this project. Samples of marine clays treated with lime and PAM are prepared and stored in moisture room in NTU and tested to determine the shear strength of treated marine clay at 7,14 and 28 days. Permeability samples of marine clay treated with lime and PAM are also tested over a period of 28 days using GDS system. One-dimensional consolidation test is also carried out to investigate the effect of different chemical content on marine clay’s compression and recompression index. Based on the test results in this project, the shear strength of marine clay treated with lime increased with increasing lime content and number of curing days. The permeability value of the lime treated marine clay shows increasing trend from 1.44 x 10-8 m/s to 3.71 x 10-8 m/s, while PAM treated marine clay shows increasing trend, from 8.71 x 10-10 m/s to 2.0710-9 m/s.